Toward an Executive Origin for Acquired Phonological Dyslexia: A Case of Specific Deficit of Context-Sensitive Grapheme-to-Phoneme Conversion Rules - Noémie Auclair-Ouellet; Marion Fossard; Marie-Catherine St-Pierre; Joël Macoir (Behavioural Neurology)
Phonological dyslexia is a written language disorder characterized by poor reading of nonwords when compared with relatively preserved ability in reading real words. In this study, we report the case of FG, a 74-year-old man with phonological dyslexia. The nature and origin of his reading impairment were assessed using tasks involving activation and explicit manipulation of phonological representations as well as reading of words and nonwords in which the nature and complexity of grapheme-to-phoneme conversion rules (GPC rules) were manipulated. FG also underwent an extensive neuropsychological assessment battery in which he showed impaired performance in tests exploring verbal working memory and executive functions. FG showed no phonological impairment, and his performance was also largely unimpaired for reading words, with no effect of concreteness, grammatical class, morphological complexity, length or nature and complexity of the GPC rules. However, he showed substantial difficulties when asked to read nonwords with contextual GPC rules. The contribution of FG’s executive deficits to his performance in reading is discussed.